Cu-Ce mixed oxides supported on Al-pillared clay: effect of method of preparation on catalytic activity in the preferential oxidation of carbon monoxide - Ramaswamy, Veda; Malwadkar, Sachin S.; Chilukuri, Satyanarayana V. (Applied Catalysis B-Environmental, 2008)
The possibility of using Al-pillared montmorillonite (Al-PILC) clay as a high-surface-area support for CuO-CeO2-based catalysts has been investigated. The preparation of the samples was done by three different methods, viz., amorphous citrate route (ACR), deposition precipitation (DP) and wet impregnation method (WIM). Samples with different CuO-CeO2 loadings (10-50 wt.%) were prepared by each of the three methods. The catalytic activity of these samples was investigated for the preferential oxidation (PROX) of carbon monoxide (CO) in excess of H-2. The samples prepared by DP and WIM methods show better activity than the samples prepared by ACR method. At low Cu content, the samples prepared by DP method have a slight edge over samples prepared by WIM method. The DP-30 sample shows a very high CO conversion of 96.1% at 423 K. A higher dispersion of CuO-CeO2 on pillared montmorillonite clay and better reducibility of copper oxide species may be responsible for the good activity of these samples even at lower reaction temperatures. A higher O-2/CO ratio increased the CO conversion but led to a reduction in oxidation selectivity. No methanation of CO or CO2 was observed at the reaction temperature. These CuO-CeO2/Al-PILC samples could be considered as comparable in performance with supported noble metal catalysts for the preferential oxidation of CO in excess hydrogen. (c) 2008 Elsevier B.V. All rights reserved.
Keywords: Alumina-pillared clay; Clay-supported CuO-CeO2; CuO-CeO2; PROX of CO